2017
DOI: 10.4103/ijdr.ijdr_35_16
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the multitude of risk factors associated with early childhood caries

Abstract: The prevalence of ECC was seen in almost a quarter of the population with a high deft. A significant relation was associated only with the feeding duration and lack of prenatal oral health counseling provided to parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Among children, 11.8% had an associated pathology and 7.8% had long-term treatment. Although these values are lower than those in other studies [ 25 , 26 ], long-term medication is a risk factor for developing early caries. According to a retrospective cohort study conducted in Taiwan, children with asthma and receiving medications had higher dental caries prevalence and higher rate of severe caries than children without asthma [ 27 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Among children, 11.8% had an associated pathology and 7.8% had long-term treatment. Although these values are lower than those in other studies [ 25 , 26 ], long-term medication is a risk factor for developing early caries. According to a retrospective cohort study conducted in Taiwan, children with asthma and receiving medications had higher dental caries prevalence and higher rate of severe caries than children without asthma [ 27 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Parents, who are the closest caregivers to their children, have great power to influence their children’s behaviour in life [41, 42]. One study showed that the lack of sharing oral health knowledge with their children by parents was a factor associated with caries [5, 43]. Therefore, we encourage parents to provide oral health guidance to their children as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [27] investigated the factors related to the susceptibility of early childhood caries in 392 children; they found significant differences in three factors: eating too many sweets each day, brushing before and after sleeping, and parents helped to brush. However, they also found a significant relation between the parents' level of education and oral health understanding and the ECC.…”
Section: Discussionmentioning
confidence: 99%